CONTENTS OF REGULATORY T-CELLS IN PERIPHERAL BLOOD AND ENDOMETRIAL TISSUE IN DYNAMIC OF MENSTRUAL CYCLE - N. A. Khonina; N. V. Seledtsova; M. A. Tikhonova; T. V. Ovsyannikova; E. R. Chernykh (Acta Biomedica Scientifica, 2012)
The maintenance of CD4+CD25+/high and CD4+CD25+CD127 — regulatory T-cells in a peripheral, menstrual blood and an endometrial tissue in different phases of a menstrual cycle is investigated. It is shown that in a phase of average secretion the number of regulatory T-cells is increased. Thus quantity of CD4+CD25+increased in peripheral circulation, and in an endometrial tissue number of CD4+CD25+CD127- cells grew.